2009
DOI: 10.1027/1618-3169.56.5.361
|View full text |Cite
|
Sign up to set email alerts
|

It Takes Just One Word to Quash a SNARC

Abstract: Our directional reading habit seems to contribute to the widely reported association of small numbers with left space and larger numbers with right space (the spatial-numerical association of response codes, SNARC, effect). But how can this association be so flexible when reading habits are not? To address this question, we asked bilingual Russian-Hebrew readers to classify numbers by parity and alternated the number format from trial to trial between written words and Arabic digits. The number words were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 21 publications
(35 reference statements)
4
79
2
2
Order By: Relevance
“…This effect seems to depend on relative, and not absolute, numerical magnitude, such that the same numbers (e.g., 4 and 5) can be associated with left-hand responses, when used as the smallest numbers in the presented range (e.g., 4-9), and with the right-hand responses, when used as the largest numbers in the presented range (e.g., 0-5; Dehaene et al, 1993;Fias, Brysbaert, Geypens, & d'Ydewalle, 1996). Moreover, the SNARC effect can be easily reversed (or 4 NUMBER RANGE EFFECT diluted) by manipulating the task instructions (e.g., Bächtold, Baumüller, & Brugger, 1998), incompatible spatial mapping/positioning (e.g., Fischer, Mills, & Shaki, 2010;Fischer, Shaki, & Cruise, 2009;Notebaert, Gevers, Verguts, & Fias, 2006;Shaki & Fischer, 2008) and memory requirements or load (e.g., Lindemann, Abolafia, Pratt, & Bekkering, 2008;2011;van Dijck, Gevers, & Fias, 2009). …”
Section: Number Range Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect seems to depend on relative, and not absolute, numerical magnitude, such that the same numbers (e.g., 4 and 5) can be associated with left-hand responses, when used as the smallest numbers in the presented range (e.g., 4-9), and with the right-hand responses, when used as the largest numbers in the presented range (e.g., 0-5; Dehaene et al, 1993;Fias, Brysbaert, Geypens, & d'Ydewalle, 1996). Moreover, the SNARC effect can be easily reversed (or 4 NUMBER RANGE EFFECT diluted) by manipulating the task instructions (e.g., Bächtold, Baumüller, & Brugger, 1998), incompatible spatial mapping/positioning (e.g., Fischer, Mills, & Shaki, 2010;Fischer, Shaki, & Cruise, 2009;Notebaert, Gevers, Verguts, & Fias, 2006;Shaki & Fischer, 2008) and memory requirements or load (e.g., Lindemann, Abolafia, Pratt, & Bekkering, 2008;2011;van Dijck, Gevers, & Fias, 2009). …”
Section: Number Range Effectmentioning
confidence: 99%
“…Future studies can test whether such effects can be found at the level of a single trial (cf. Fischer et al, 2009) or whether they are constrained to manipulations made at the block level. Additional work can focus on the question of exactly how malleable the properties of the mental number line can be, depending on the distributional properties of the numbers processed for a particular task.…”
Section: Number Range Effectmentioning
confidence: 99%
“…Unfortunately for studies of SNARC-like effects in sequence-space synaesthesia, it has been increasingly argued that spatial stimulus-response congruity effects, such as the SNARC effect, may reflect intentional, short-term and task-specific spatial associations, which may even be verbally mediated, rather than reflect the detailed layout of persistent automatised spatial associations (Caessens et al, 2005;Fischer, 2006;Fischer et al, 2009Fischer et al, , 2010Gevers et al, 2006;Shaki and Fischer, 2008;Proctor and Vu, 2002;van Dijck et al, 2009).…”
Section: Concerns With the Evidence From Snarc Effects: Automatic Spamentioning
confidence: 99%
“…Second, even to the extent that non-verbal spatial representations are involved in the SNARC effect, these appear to be highly flexible and context sensitive (e.g., Fischer et al, 2010;Fischer et al, 2009;Shaki and Fischer, 2008). They may also be mediated by standard processes of visuospatial imagery.…”
Section: Concerns With the Evidence From Snarc Effects: Automatic Spamentioning
confidence: 99%
“…This, of course, depends on the degree of proficiency in the second language . Moreover, in research on bilingual people whose two languages have opposite writing direction (for instance, Hebrew and Russian), an oscillating change of the SNARC effect is observed when participants are asked to change the reading direction of texts expressed in languages with opposite writing directions (Shaki and Fischer 2008;Fischer et al 2009). …”
Section: The Cultural Factors Of the Flexibility Of Snarc Effectsmentioning
confidence: 99%